Stability of three-phase ternary-eutectic growth patterns in thin sample. (1st May 2016) - Bottin-Rousseau, Sabine; Şerefoğlu, Melis; Yücetürk, Sinan; Faivre, Gabriel; Akamatsu, Silvère
Abstract: Near-eutectic ternary alloys subjected to thin-sample directional solidification can exhibit stationary periodic growth patterns with an ABAC repeat unit, where A, B, and C are the three solid phases in equilibrium with the liquid at the eutectic point. We present an in-situ experimental study of the dynamical features of such patterns in a near-eutectic In–In2 Bi–Sn alloy. We demonstrate that ABAC patterns have a wide stability range of spacing λ at given growth rate. We study quantitatively the λ -diffusion process that is responsible for the spacing uniformity of steady-state patterns inside the stability interval. The instability processes that determine the limits of this interval are examined. Qualitatively, we show that ternary-eutectic ABAC patterns essentially have the same dynamical features as two-phase binary-eutectic patterns. However, lamella elimination (low- λ stability limit) occurs before any Eckhaus instability manifests itself. We also report observations of stationary patterns with an [AB]m [AC]n superstructure, where m and n are integers larger than unity. Graphical abstract: